2019
DOI: 10.2224/sbp.8559
|View full text |Cite
|
Sign up to set email alerts
|

Choosing an equitable or efficient option: A distribution dilemma

Abstract: We conducted a 3 × 3 × 2 experiment to verify the moral preference hypothesis and extend the boundary conditions of the moral frame effect. Participants played a trade-off game (TOG), in which they unilaterally choose between an equitable or efficient option. We manipulated the labeling of the options to describe the equitable versus efficient option as morally right, and controlled the amount of the stakes and division schemes in the TOG. We found there was a significant effect of moral frame when stakes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Capraro and Rand (2018) found that the moral frame can significantly influence the distributor's equal and efficient preferences [14]. Huang et al (2019) found that when participants' interest changes greatly, the effect of the moral frame is more significant [15]. However, these two studies require participant responsibility for the decision whether to change the existing division scheme, which may explain the difference those results and the results of our study.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…Capraro and Rand (2018) found that the moral frame can significantly influence the distributor's equal and efficient preferences [14]. Huang et al (2019) found that when participants' interest changes greatly, the effect of the moral frame is more significant [15]. However, these two studies require participant responsibility for the decision whether to change the existing division scheme, which may explain the difference those results and the results of our study.…”
Section: Discussionmentioning
confidence: 50%
“…If participants are not affected by maxims, regardless of the scenario, the distribute choice should be the same or similar, and there should be no significant difference in the equal preference of the scenarios. However, according to the nudging theory, availability heuristics, and empirical research [14,15,23], we speculate that participants' equal preference is affected by relevant information, such as maxims and social norms. Therefore, we proposed the following hypothesis:…”
Section: Study Overviewmentioning
confidence: 90%
See 2 more Smart Citations
“…In this paper, we investigate the influence of reputational incentives on sensitivity to moral frames in the context of the Trade-Off Game (TOG), an economic decision problem that forces decision-makers to decide between competing values of equality and efficiency. We chose to investigate decisions in the TOG because there is a robust body of evidence that, in experiments where reputation is not at stake, moral framing has a substantial influence on TOG decisions (Capraro & Rand, 2018;Tappin & Capraro, 2018;Capraro, Rodriguez-Lara, & Ruiz-Martos, 2020;Huang, Lei, Xu, Yu, & Shi, 2019).…”
Section: Our Contributionmentioning
confidence: 99%